2018
DOI: 10.17994/it.2018.16.1.52.10
|View full text |Cite
|
Sign up to set email alerts
|

New Dilemmas of International Banking Standards

Abstract: Для последних нескольких лет характерна активная разработка и внедрение новых регуляторных стандартов, имеющих целью предупреждение кризисов и повышение банковской стабильности. При безусловной направленности на поддержание финансовой устойчивости банков практическая реализация этих стандартов не столь однозначна. Настоящая статья посвящена анализу влияния новых требований в области регулирования капитала, введения дополнительного показателя рисковой нагрузки на основе финансового левериджа на бизнес-модель кр… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…I. Larionova, E. Meshkova [17] analyzed the effectiveness of using financial leverage in order to increase the financial stability of Russian banks. Based on the analysis, the authors concluded that due to a significant excess of the planned level of financial leverage, banks compiled a high-risk portfolio of assets, not captured by the new standard.…”
Section: Literature Reviewmentioning
confidence: 99%
“…I. Larionova, E. Meshkova [17] analyzed the effectiveness of using financial leverage in order to increase the financial stability of Russian banks. Based on the analysis, the authors concluded that due to a significant excess of the planned level of financial leverage, banks compiled a high-risk portfolio of assets, not captured by the new standard.…”
Section: Literature Reviewmentioning
confidence: 99%